Multi-variable extreme seeking control for efficient operation of sub-cooler vapor injection trans-critical CO2 heat pump water heater. (5th February 2021) - Cui, Ce; Ren, Jiahang; Song, Yulong; Yin, Xiang; Wang, Wenyi; Yang, Xu; Cao, Feng
Highlights: Multi-variable ESC control. Sub-cooler vapor injection trans-critical CO2 heat pump water heater. Real-time minimization of power consumption; Modelica based model. Abstract: It has been promising to utilize the vapor injection method to enhance the performance of the transcritical CO2 heat pump under the working condition of low ambient temperature and high water inlet temperature. The complicated optimization process of both the discharge pressure and the medium pressure has prevented the system from further application. We introduce the multi-variable extreme seeking control strategy to realize the real-time power consumption minimization of the sub-cooler vapor injection trans-critical CO2 system. The multi-variable ESC controller takes the power consumption as the feedback, the discharge pressure and the medium pressure setpoint as the manipulated inputs. The control strategy is evaluated on a dynamic simulation model for the proposed system using Dymola and ThermalSystems from TLK-Thermo, GmbH. The simulation is conducted under the working conditions of the fixed design condition, the staircase of water inlet temperature and the realistic ambient temperature profile. Simulation results show that ESC can optimize the discharge pressure and intermediate pressure for high system efficiency with good steady-state and transient performance.